Bearing capacity of composite ground with soil-cement columns under earth fills : physical and numerical modeling - Ni, Pengpeng (2021)
Soil-cement columns are widely used to improve soft ground, and the bearing capacity of the formed composite ground is a key design parameter. The currently employed design method was developed for composite grounds under rigid footings, whilst the bearing capacity behavior of composite grounds under earth fills with different degrees of stiffness has rarely been investigated. Hence, the present study attempts to fill this gap. In this investigation, 1-g laboratory model tests are conducted to compare the bearing capacity behavior of composite grounds under a rigid footing and under embankment fill, based on which a numerical model that can capture the strain-softening behavior of soil-cement columns is established. The calibrated numerical model is further employed to perform 144 analyses. The results indicate that the failure mode of composite grounds differs for different types of earth fills: soil failure occurs prior to column failure under soft clay and dredged slurry, whereas column failure is the primary failure mode for composite grounds under embankment fill. This difference in failure mode of composite grounds can be explained using soil arching theories. For different failure modes, different bearing capacity efficiency factors should be used in design.